Virginia Woolf’s “Modernist Renaissance” in “Anon”: A Singular Counter-History - Anne Besnault (Sillages Critiques)
Virginia Woolf’s relationship with her early-modern predecessors is now a well-established field of study. As Juliet Dusinberre argues, with the Renaissance Woolf “connected herself with a life which included her own rebirth as writer and reader through the recovery of female forebears”; the period was also a laboratory of her revolt against Victorian patriarchy. It is this very notion of rebirth that Woolf rewrites in her drafted essay “Anon,” the unfinished chapter of her “Common History Book” that she left in the form of an incompletely revised typescript in 1940 and that was posthumously published. In the months preceding her death, the Second World War was putting all ideas of renewal at bay: to rewrite Britain’s cultural history, whether in the form of a play-poem with Between the Acts (1940) or in the form of a critical literary history had become an urgent act of hope in the midst of despair. That Woolf sees the “Renaissance” in “Anon” as a breaking point is obvious; that she sees it as the promise of a democratic future celebrating the origins of the notion of “novelty” and the birth of a national culture is less evident. The aim of this article is to examine the symbolic murder that Woolf stages in her essay, that of Anon, the anonymous female or male poet, by the invention of the printing press, while reading in context Woolf’s counter-narrative grounded in a singular, historiographical cycle of life and death.